Analysis of the Benefits and Risks of Digital Payments on Cash Receipts at Hotels in Bali - Dewi, Ni Luh Gede Sri Mulya; Widawati, Ida Ayu Putri; Septiviari, Anak Agung Istri M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The use of digital payments in cash receipts at hotels in Bali has increased in the period 2021 to 2023. Cash receipts with digital payments are processed by accounts receivable and income audit. This study aims to determine the benefits and risks of cash receipts via digital payments at Hotel